Personal Digital Assistant (PDA) Based Client/Server Data Collection System - Balasubramaniam, Nagaletchumi (2004)
Nowadays, in the competitive world, mobility plays an important role in the business and daily lives. Personal Digital Assistant (PDA) is one of the most actively developing areas in computer systems technology. PDAs start replacing PCs especially where PCs and Internet/Network technology do no reach. PDAs are being used to access, monitor, and control database management system of organizations. This work investigates the issues involved in designing and developing a PDA based client/server data collection system for an inventory control of a hypermarket. This thesis also provides a comprehensive discussion on the software and hardware aspects of the data collection system. Personal Digital Assistant (PDA) module is used as a base unit in this research. Application software has been developed for the PDA and PC. Interfacing the software provides the system to function in a client server environment. The performance of the system in terms of memory usage by the PDA and synchronization time has been studied, as these are important parameters from user point of view. Further integration of PDA with wireless technologies and other peripheral devices are discussed as future work of the research.